2022
DOI: 10.1136/archdischild-2021-322644
|View full text |Cite
|
Sign up to set email alerts
|

Childhood, teenage and young adult cancer diagnosis during the first wave of the COVID-19 pandemic: a population-based observational cohort study in England

Abstract: ObjectiveTo investigate childhood, teenage and young adult cancer diagnostic pathways during the first wave of the COVID-19 pandemic in England.DesignPopulation-based cohort study.Setting and participantsQResearch, a nationally representative primary care database, linked to hospital admission, mortality and cancer registry data, was used to identify childhood, teenage and young adult cancers (0–24 years) diagnosed between 1 January 2017 and 15 August 2020.Main outcomesMain outcomes of interest were: (1) numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…They might relate to the fact that stay-at-home advice was addressed mainly to seniors. Contrary to an English study, which reported a decrease in new childhood cancer diagnoses ( 29 ), neither our analysis nor Canadian ( 30 ) or German ( 31 ) reports confirmed such a trend.…”
Section: Discussioncontrasting
confidence: 99%
“…They might relate to the fact that stay-at-home advice was addressed mainly to seniors. Contrary to an English study, which reported a decrease in new childhood cancer diagnoses ( 29 ), neither our analysis nor Canadian ( 30 ) or German ( 31 ) reports confirmed such a trend.…”
Section: Discussioncontrasting
confidence: 99%
“…Worldwide, substantial disruptions in pediatric cancer diagnosis and management were described in the first pandemic wave, particularly in low- and middle-income countries. 74 Whereas a study conducted in the UK reported a significant reduction in cancer diagnoses during the first wave, 75 however, two studies from Canada and Germany 76 , 77 did not find a decrease in the first pandemic year. These heterogeneous published data, combined with the insufficient statistical power of our pediatric series which did not allow us to analyze incident cases according to pandemic waves for all tumor types, mean that our estimates must be interpreted with great caution.…”
Section: Discussionmentioning
confidence: 96%
“…We are confident that tumour volume has been accurately measured and registered, since the evaluation of volume reduction after pre‐operative chemotherapy are among the endpoints of the ongoing UMBRELLA study. Previously pursued, similar studies had been conducted by paediatric cancer registries with various cancers, or single‐centred experience from a regional institute 9,20,32,45,46 . In the latter studies, influence of the pandemic on tumour characteristics, delay of diagnosis and starting treatment of the paediatric cancers could not be taken into account as specifically.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned reports reflect mostly either adult cancer and/or national cancer registry perspectives. Therefore, the possibility to ascertain the impact on individual cancer types and organisation of care for subsets of patients on a global scale is still limited 23,29–32 . The paediatric oncology setting in general is different with respect to referral speed, based on the need for rapid management of the most highly proliferating cancer types in childhood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation